The international platform of registered systematic review and meta-analysis protocols (INPLASY) at 3 years: an analysis of 4,658 registered protocols on inplasy.com, platform features, and website statistics - Canellas, João Vitor dos Santos; Ritto, Fabio Gamboa; Rodolico, Alessandro; Aguglia, Eugenio; Fernandes, Gustavo Vicentis de Oliveira; Figueredo, Carlos Marcelo da Silva; Vettore, Mario Vianna (Frontiers in Research Metrics and Analytics, 2023)
Background: INPLASY® is an international platform for registering systematic reviews and metaanalysis protocols that was launched in March 2020. INPLASY® provides an online database in which the protocols are maintained as permanent public records and can be accessed on its website (www.inplasy.com).Methods: We described the database features and registered information of all records published since the launch of the registry on March 31, 2023. Additionally, the website statistics dataset was analyzed to explore the user experience and promote data transparency.Results: Four thousand six hundred fifty-eight records were registered in INPLASY®, and more than 94% of the protocols were published within 24 h. Most of the submissions were from China, followed by Portugal, Taiwan, Malaysia, and Brazil. The INPLASY® website received 386,395 page views from 64,568 visitors during the first three years. The accesses were obtained from 170 countries. Most of the accesses were from China, followed by the US, the UK, and Portugal. The review status ''completed and published'' was observed in 898 protocols, and these studies were published in 372 different scientific peer-reviewed journals. The INPLASY® features include: (i) INPLASY® identifier, a unique protocol number; (ii) the digital object identifier (DOI) number, the URL of the protocol linked to a specific DOI; (iii) ORCID update, INPLASY® updates the authors'